2001
DOI: 10.3354/dao045229
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of cataracts in seawater farmed Atlantic salmon Salmo salar

Abstract: Cataracts in farmed Atlantic salmon have been known for many years, but the aetiology and importance of the disease have not been clarified. A cross-sectional field study of 51 cages of Atlantic salmon at 49 randomly selected sea sites was performed during the summer of 1998. The target population was spring and autumn entry groups of the 1997 generation salmon. Approximately 15 fish from each cage, altogether 777 fish, were autopsied by the same person. Each eye of the fish was scored for cataracts on a scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Aquaculture industries promote increasing individual growth (Thodesen and Gjedrem, 2006;Asche and Bjørndal, 2011) as it increases feed conversion efficiency, which in turn increases sustainability and economic efficiency (Cook et al, 2000). Rapid growth has previously been shown to increase the incidence of cataracts (Ersdal et al, 2001), but the present study is the first to show that it permanently deforms otoliths. If fish welfare is negatively impacted through impaired hearing (Reimer et al, 2016), the industry could reduce growth rates to prevent abnormal vaterite formation.…”
Section: Discussionmentioning
confidence: 40%
“…Aquaculture industries promote increasing individual growth (Thodesen and Gjedrem, 2006;Asche and Bjørndal, 2011) as it increases feed conversion efficiency, which in turn increases sustainability and economic efficiency (Cook et al, 2000). Rapid growth has previously been shown to increase the incidence of cataracts (Ersdal et al, 2001), but the present study is the first to show that it permanently deforms otoliths. If fish welfare is negatively impacted through impaired hearing (Reimer et al, 2016), the industry could reduce growth rates to prevent abnormal vaterite formation.…”
Section: Discussionmentioning
confidence: 40%
“…This has been reported to be the case in fish suffering from nonparasitic cataracts (Ersdal et al, 2001). Similarly, Seppä-nen et al (2008) showed a significant phenotypic relationship in landlocked Atlantic salmon, Salmo salar, between parasitism and individual growth (r ¼ À0.376, n ¼ 50 fish, Po0.01), such that fish with a higher parasite load and more severe cataracts suffered from reduced growth.…”
Section: Discussionmentioning
confidence: 89%
“…Fish swimming in the upper water body will probably face fewer parasites released from bottom-detached snails than fish swimming in lower water body. Although our results do not imply costs of resistance or tolerance we cannot totally exclude the possibility that the negative impact of cataract formation on growth caused directly by reduced eyesight (Ersdal et al, 2001) is masking the potential costs of resistance or tolerance on growth.…”
Section: Discussionmentioning
confidence: 89%
“…This ubiquitous parasite causes cataracts, reduces fish vision, and may even induce total blindness [78]. A marginal effect of seasonality on the abundance of this species was observed.…”
Section: Discussionmentioning
confidence: 99%